Child Growth and Neurodevelopment: A Literature Review as a Basis for Early Detection of Developmental Disorders - Setyaningtyas, Rahma Julia (Media Keperawatan Indonesia, 2025)
The golden age is a critical phase of brain architecture formation that determines the future quality of child growth and development. Early detection of developmental disorders is often delayed due to an exclusive focus on physical indicators, such as stunting, without the adequate integration of neurobiological monitoring. This study aims to analyze the reciprocal relationship between child growth and brain development as a conceptual foundation for developing strategies for the early detection of developmental disorders. This study employed a literature review design with a thematic approach, utilizing Scopus and PubMed databases for articles published between 2021 and 2025. The analysis involved selecting 11 final articles that met the inclusion criteria based on the PRISMA flow diagram. The analysis identified three main themes: the impact of nutritional status and stunting on brain architecture, instruments and technologies for early detection, and the effectiveness of early stimulation interventions. Data synthesis indicates that physical recovery alone is insufficient to restore lost cognitive function without intensive brain development stimulation. This review concludes that stunting reflects structural brain deficits rather than mere physical growth retardation, rendering the separation of nutritional monitoring and neuroscience obsolete. We recommend a paradigm shift toward an integrated brain-protection model that incorporates neurodevelopmental screening technologies into primary care starting from the prenatal phase. Enhancing health professionals' competence in neurobehavioral assessment is crucial to ensure timely interventions during the critical window of brain plasticity.